Efficiency of two cation exchange methods for isolating lactoperoxidase and lactoferrin from Gouda and Cheddar cheese whey - Bester, B.H. (University of Pretoria, 2013)
Dissertation (MSc (Food Science))--University of Pretoria, 2005.